Reconversion du tribunal religieux « Dar Echaraa » dans la médina de Sousse (Tunisie) en un espace culturel contemporain - Zeineb Youssef (In Situ)
« Dar Echaraa » or the ancient religious tribunal of the Medina of Sousse remains a historic monument from the 17th century, symbolic and emblematic with its heritage value and its original architectural qualities. It is preserved until nowadays thanks to the initiatives of the local community, national and international institutions. The building is composed of wide courtyard, sober exterior fronts and a richly decorated entrance door. It is approachable through stairs, and around the square courtyard whose walls are covered with carved and ochre-coloured stones, several rooms are arranged. Dar Echaraa is a valuable landmark in the Medina of Sousse, for the inhabitants, the users and the visitors wandering daily in the alleys of the historic centre. Since the secularisation and unification of Tunisian justice system and from the time when the promulgation of the personal status code occurred on 13 August, 1956, Dar Echaraa has lost all its judicial and administrative functions as a court of justice. This architectural jewel, abandoned for many decades, depreciated and ruined, ended up being forgotten. In the 90s and thanks to the privilege of recognition of the Medina of Sousse as a World Heritage site by UNESCO, Dar Echaraa witnessed important restoration project launched by the municipality of Sousse with close collaboration with the Association for the Safeguarding of the Medina (ASM), and the technical and financial support provided by the International Association of Francophone Town Halls (AIMF). Consequently, the building has been restored, maintained and then converted into a contemporary cultural centre. Thanks to this architectural conversion, Dar Echaraa has acquired a new contemporary expression, and the former charaic tribunal, threatened to be ruined, has become a privileged destination hosting cultural and scientific events, seminars, and thus it often hosts many visitors. Therefore, what are the impacts of this architectural conversion on the ancient tribunal of the Medina? How to assess this requalification and its impacts on the process of heritagisation of the monument?The present research consists on assessing the conversion and the requalification of Dar Echaraa by comparing between the old and current states of the monument. Thus, we are describing thoroughly the changes of a place that was once a symbol of the rigor of justice and jurisprudence and that has become a space of culture and leisure, where sometimes hundreds of visitors come to assist, in a friendly atmosphere, to the various events that take place there.